PENINGKATAN SIKAP KONSENTRASI DAN HASIL BELAJAR MATERI PENJUMLAHAN PENGURANGAN MENGGUNAKAN MODEL PBL DAN MEDIA KONKRET KELAS 2 SDK SANG TIMUR YOGYAKARTA - Maharani, Agnes; Sumarah, Ignatia Esti (JS (JURNAL SEKOLAH), 2024)
Abstract: From the results of observations and interviews with grade 2 teachers at SDK Sang Timur Yogyakarta, researchers found that grade 2 students were still lacking in an attitude of concentration in learning. In addition, the learning outcomes of grade 2 students in mathematics subjects on addition and subtraction material still have not reached the word complete (KKM) with a KKM value of 75. Therefore, researchers conducted Classroom Action Research (PTK) with the methods used were observation, interviews, tests and documentation studies. The tests used in this study were pre-test and post-test to determine the level of understanding of students related to learning materials. The number of subjects in this study were 16 students consisting of 6 male students and 10 female students in class 2. The results of this study indicate an increase in the attitude of learning concentration and learning outcomes of students in mathematics subjects on the material of addition and subtraction of numbers. The percentage increase in the attitude of learning concentration increased significantly from cycle 1 to cycle 2 with an increase from cycle 1 to cycle 2 in the very concentration category from 25% to 31.25%, the concentration category is 31.25% to 43.7%.In addition, the learning outcomes of students also increased from pre-cycle with a percentage of 50% increasing to cycle 1 with a percentage of 62.5% and increasing to cycle 2 with a percentage of 81.25%. Keyword: Learning Concentration Attitude, Learning Results, Mathematics, Class 2Abstrak: Dari hasil observasi dan wawancara dengan guru kelas 2 SDK Sang Timur Yogyakarta, peneliti mendapatkan hasil bahwa peserta didik kelas 2 masih kurang dalam sikap berkonsentrasi dalam pembelajaran. Selain itu, hasil belajar peserta didik kelas 2 dalam mata pelajaran matematika materi penjumlahan dan pengurangan masih belum mencapai kata tuntas (KKM) dengan nilai KKM 75. Maka dari itu, peneliti melakukan Penelitian Tindakan Kelas (PTK) dengan metode yang digunakan adalah observasi, wawancara, tes dan studi dokumentasi. Tes yang digunakan dalam penelitian ini adalah pre-test dan post-test untuk mengetahui tingkat pemahaman peserta didik terkait materi pembelajaran. Jumlah subjek dalam penelitian ini adalah 16 peserta didik yang terdiri dari 6 peserta didik laki-laki dan 10 peserta didik perempuan kelas 2.. Hasil dari penelitian ini menunjukkan adanya peningkatan sikap konsentrasi belajar dan hasil belajar peserta didik pada mata pelajaran matematika materi penjumlahan pengurangan bilangan. Presentase peningkatan sikap konsentrasi belajar meningkat signifikan dari siklus 1 ke siklus 2 dengan peningkatan yang terjadi pada siklus 1 ke siklus 2 pada kategori sangat konsentrasi yaitu dari 25% menjadi 31,25%, kategori konsentrasi yaitu 31,25 % menjadi menjadi 43,7%.. Selain itu, pada hasil belajar peserta didik juga mengalami peningkatan dari pra siklus dengan presentase 50% meningkat ke siklus 1 dengan presentase 62,5% dan meningkat ke siklus 2 dengan presentase 81,25%.Kata Kunci: Sikap Konsentrasi Belajar, Hasil Belajar, Matematika, Kelas 2